Classification and function of small open reading frames. - Couso, J.P.; Patraquim, P. (Nature Reviews. Molecular Cell Biology, 2017)
Small open reading frames (smORFs) of 100 codons or fewer are usually - if arbitrarily - excluded from proteome annotations. Despite this, the genomes of many metazoans, including humans, contain millions of smORFs, some of which fulfil key physiological functions. Recently, the transcriptome of Drosophila melanogaster was shown to contain thousands of smORFs of different classes that actively undergo translation, which produces peptides of mostly unknown function. Here, we present a comprehensive analysis of smORFs in flies, mice and humans. We propose the existence of several functional classes of smORFs, ranging from inert DNA sequences to transcribed and translated cis-regulators of translation and peptides with a propensity to function as regulators of membrane-associated proteins, or as components of ancient protein complexes in the cytoplasm. We suggest that the different smORF classes could represent steps in gene, peptide and protein evolution. Our analysis introduces a distinction between different peptide-coding classes of smORFs in animal genomes, and highlights the role of model organisms for the study of small peptide biology in the context of development, physiology and human disease.